Mechanisms of arterial remodeling: lessons from genetic diseases - Van Varik, Bernard; Rennenberg, Roger; Reutelingsperger, Chris; Kroon, Abraham; de Leeuw, Peter; Schurgers, Leon J. (Frontiers in Genetics, 2012)
Vascular disease is still the leading cause of morbidity and mortality in the Western world, and the primary cause of myocardial infarction, stroke, and ischemia. The biology of vascular disease is complex and still poorly understood in terms of causes and consequences. Vascular function is determined by structural and functional properties of the arterial vascular wall. Arterial stiffness, that is a pathological alteration of the vascular wall, ultimately results in target-organ damage and increased mortality. Arterial remodeling is accelerated under conditions that adversely affect the balance between arterial function and structure such as hypertension, atherosclerosis, diabetes mellitus, chronic kidney disease, inflammatory disease, lifestyle aspects (smoking), drugs (vitamin K antagonists) and genetic abnormalities (e.g. pseudoxanthoma elasticum, Marfan’s disease). The aim of this review is to provide an overview of the complex mechanisms and different factors that underlie arterial remodeling, learning from single gene defect diseases like PXE, and PXE-like, Marfan’s disease and Keutel syndrome in vascular remodeling.